Adsorption of Methylene Blue Dye using Fe3O4 Magnetized Natural Zeolite Adsorbent - Donatus Rendo (Jurnal Kimia Sains dan Aplikasi, 2021)
Preparation and characterization of Fe3O4 magnetized natural zeolite adsorbent for adsorption of methylene blue dye have been carried out. Natural zeolite/Fe3O4 adsorbent preparation was carried out using coprecipitation of Fe2+ and Fe3+ ions (1: 2 mol ratio) on the natural zeolite surface. Characterization was carried out using X-Ray Diffraction (XRD), Fourier Transform Infra-Red (FTIR), and Scanning Electron Microscopy (SEM) to determine the effect of Fe3O4 on the natural zeolite surface. UV-Vis spectroscopy was used to determine the concentration of methylene blue after the adsorption process. The characterization results showed that Fe3O4 was successfully embedded in the natural zeolite without damaging the natural zeolite's crystallinity. Natural zeolite/Fe3O4 adsorbent showed easy separation from water medium after the adsorption process. The optimum conditions for adsorption were achieved at the contact time of 60 minutes, and the initial concentration of methylene blue was 30 ppm with an adsorbent mass of 25 mg. Adsorption kinetics followed pseudo-second-order reaction kinetics, and adsorption isotherm followed Langmuir isotherm with an adsorption capacity of 32.258 mg/g.